Pengaruh PBL dengan Strategi HPC terhadap Literasi Emosional dan Keterampilan Pemecahan Masalah Biologi Siswa: Studi Pada Sistem Peredaran Darah Manusia - Leasa, Marleny; Pelamonia, Johanes (Biosfer: Jurnal Pendidikan Biologi, 2024)
Emotional literacy as a new 21st-century literacy is one-factor influencing student learning success. This study aims to analyze the differences in emotional literacy and problem-solving skills in Problem-Based Learning (PBL) model learning with Homogeinity psycho cognition (HPC) Strategy and PBL. This study included quasi-experiment research with a pretest-postest nonequivalent control group design. The research sample was 75 fifth-grade students taken randomly from several elementary schools in the Nusaniwe Sub-District based on the placement test. The research instruments were an emotional literacy questionnaire and a problem-solving skills test instrument consisting of 20 statement items and 8 problem items related to the human circulatory system. Data analysis used the Mann-Whitney U Test and one-way ANCOVA. The results showed no difference in emotional literacy between the treatment group (PBL with HPC strategy) and the control group (PBL). The ANCOVA test results concluded that students' problem-solving skills in the PBL model with the HPC strategy were superior to those in the PBL model. This finding helps develop appropriate and strategic science-biology learning in elementary schools.